Influence of Nutrient (NPK) Factors on Growth, and Pharmacodynamic Component Biosynthesis of Atractylodes chinensis: An Insight on Acetyl-CoA Carboxylase (ACC), 3-Hydroxy-3-Methylglutaryl-CoA Reductase (HMGR), and Farnesyl Pyrophosphate Synthase (FPPS) Signaling Responses - Sun, Jin; Luo, Haoming; Jiang, Yuxin; Wang, Lijuan; Xiao, Chunping; Weng, Lili (Frontiers in Plant Science, 2022)
In the planting of crops, especially medicinal plants, formula fertilization is important for improving the utilization rate of elements, soil quality, crop yield, and quality. Therefore, it is important to study targeted fertilizer application schemes for sustainable agricultural development and environmental protection. In this study, an L9(34) orthogonal design was used to conduct a field experiment to study the effects of NPK combined application on the growth and pharmacodynamic component biosynthesis of Atractylodes chinensis (DC.) Koidz. Results showed that after applying a base fertilizer at the seedling stage (late May), topdressing at the vegetative stage (late June) and fruit stage (late August) was beneficial to the growth and development of A. chinensis. High concentrations of phosphorus were conducive to the accumulation of yield and effective components, and the best harvest time was after late October. Principal component analysis (PCA) showed that the comprehensive score of T6 treatment was the highest, indicating that the optimal fertilization scheme for high yield and high quality of A. chinensis was (N2P3K1): N 180 kg·ha-1, P2O5 225 kg·ha-1, K2O 105 kg·ha-1. Signaling response analysis showed that during the growth and development of A. chinensis, the T6 fertilization scheme had clear effects on the activity and gene expression of the key enzymes acetyl-CoA carboxylase (ACC) and farnesyl pyrophosphate synthase (FPPS). Under the T4 [(N2P1K2): N 180 kg·ha-1, P2O5 75 kg·ha-1, K2O 210 kg·ha-1] fertilization scheme, activity and gene expression of the key enzyme 3-hydroxy-3-methylglutaryl-CoA reductase (HMGR) were higher. Moreover, ACC was closely related to the synthesis of the polyacetylene component atractylodin, and FPPS played an important regulatory role in the synthesis of sesquiterpene components atractylenolide II, β-eudesmol, and atractylon. In summary, the high phosphorus fertilization scheme T6 could notably increase the yield of A. chinensis, and promote the accumulation of polyacetylene and sesquiterpene volatile oils by increasing the expression of ACC and FPPS. Therefore, we postulate that the precise application of nutrients (NPK) plays a vital role in the yield formation and quality regulation of A. chinensis.